Multiscale Approach to Dairy Products Design - Díaz-Bustamante, Martha L.; Fernández-Niño, Miguel; Reyes, Luis H.; Alvarez Solano, Oscar Alberto (Frontiers in Chemical Engineering, 2022)
Dairy products are among the most popular nutritious foods in the world. Understanding the relationship between the composition, process, and structural properties at different scales (molecular, microscopic, and macroscopic) is fundamental to designing dairy products. This review highlights the need to analyze this relationship from different scales as an essential step during product design through a multiscale approach.